Clinical and pathogenetic aspects of neutrophilic bronchial inflammation in asthma patients with cold-induced airway hyperresponsiveness (literature review) - A. B. Pirogov; A. G. Prikhodko; N. A. Pirogova; J. M. Perelman (Бюллетень сибирской медицины)
The review presents data on the effect of neutrophilic bronchial inflammation on the clinical course, external respiration, and formation of the airway response to cold air in patients with asthma. According to the results of modern studies, activation of the structural and functional state of neutrophils in a mixed inflammatory pattern is associated with an increase in disease severity, more difficult achievement of asthma control, pronounced impairment of bronchial patency due to stimulation of epithelial destruction and remodeling, and development and maintenance of cold-induced airway hyperresponsiveness.The mechanisms activating the Th1 cytokine profile and oxidative and halogenation stress and determining the activity of neutrophils and persistence of chronic inflammation lead to oxidative damage to lung parenchyma and epithelial dysfunction, which contributes to cold-induced bronchoconstriction. Cytolysis and NETosis, acting as alternative pathways of neutrophil death in the airways of asthma patients, are considered in terms of final stages of induced activity of neutrophil lysosomes in the mixed asthma phenotype.